Intraformational unconformities as a record of late Miocene eustatic falls of sea level in the Pisco Formation (southern Peru). Issue 2 (13th November 2018) - Di Celma, Claudio; Malinverno, Elisa; Bosio, Giulia; Gariboldi, Karen; Collareta, Alberto; Gioncada, Anna; Landini, Walter; Pierantoni, Pietro Paolo; Bianucci, Giovanni
ABSTRACT: Field mapping and sedimentological study of outcrop sections exposed along the Ica River valley permitted the establishment of a regional allostratigraphic framework for the upper Miocene portion of the Pisco Formation. The stratigraphy of the studied interval is illustrated using a new 1:20, 000-scale geological map which reveals that this formation is a cyclical sedimentary succession composed of three fining-upward allomembers. The bounding surfaces defining each allomember are transgressively modified subaerial unconformities. They converge and merge landward into a single composite surface representing the time-transgressive lower boundary of the Pisco Formation. Accordingly, the extent of the stratigraphic gap associated with the basal unconformity varies significantly throughout the basin and increases toward the basin margins. The timing of allomember-bounding surfaces coincides with that of major oxygen-isotope maxima in the deep-sea oxygen isotopic record and matches the ages of eustatic sequence boundaries identified elsewhere, indicating glacio-eustatic falls due to the growth of Antarctica ice sheets as a viable mechanism for their development.